Wage Inequality and Family Labor Supply - Juhn, Chinhui; Murphy, Kevin M. (Journal of Labor Economics, 1997)
Using the March Current Population Surveys and the 1960 census, this article describes earnings and employment changes for married couples in different types of households stratified by the husband's hourly wage. While declines in male employment and earnings have been greatest for low-wage men, employment and earnings gains have been largest for wives of middle- and high-wage men. These findings cast doubt on the notion that married women have increased their labor supply in the recent decades to compensate for the disappointing earnings growth of their husbands.